Ozone oxidation catalyst for inorganic treatment of organic waste liquid and preparation method thereof
By using molecular sieve as a support, combining active metal oxides and modified element oxides, a heterogeneous ozone oxidation catalyst with high specific surface area and active sites was prepared, which solved the problem of insufficient mechanical strength of the catalyst and achieved efficient organic Waste liquid inorganic treatment.
Patent Information
- Application Number
- CN202411729153.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing ozone catalytic oxidation technology, the mechanical strength of heterogeneous catalysts is insufficient, resulting in low oxidation efficiency and serious catalyst loss, which increases the cost of wastewater treatment.
Using molecular sieve as a support, combining active metal oxides, modified element oxides and binders, a heterogeneous ozone oxidation catalyst with a larger specific surface area and higher active sites is prepared through high-temperature calcination and water vapor aging treatment. .
The mechanical strength and oxidation efficiency of the catalyst are improved, the life of the catalyst is extended, the COD removal rate can reach more than 90%, reducing the treatment cost.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic waste liquid treatment, and relates to an ozone oxidation catalyst for inorganic treatment of organic waste liquid and waste water and a preparation method thereof. Background Art
[0002] With the rapid development of industry, water pollution is becoming increasingly serious. In the field of deep wastewater treatment, the effective removal of difficult-to-biodegrade organic matter is a major problem. After the wastewater undergoes secondary biochemical treatment, the remaining organic matter is difficult-to-biodegrade organic matter, which is difficult to remove by conventional biochemical, physicochemical and oxidation processes. The raw materials, products and intermediates involved in its production process are more complex, and the pollutants in the wastewater produced are of various types, making it more difficult to treat, and it is difficult for enterprises to meet the discharge standards for wastewater.
[0003] Ozone O3 is a strong oxidant with a high oxidation potential of 2.07V. It can directly react with organic compounds in the form of molecular ozone. It can decompose organic pollutants into short-chain intermediates and degrade organic pollutants. It is often used in the field of industrial water treatment. Ozone oxidation technology has the advantages of strong oxidation ability, good decolorization effect, and no secondary pollution.
[0004] Ozone catalytic oxidation technology is a new water treatment technology that aims to enhance the oxidation performance of ozone and improve the utilization efficiency of ozone by catalyzing ozone oxidation reaction under the action of catalysts to completely degrade or transform the difficult-to-degrade organic components in sewage in a short time, thereby achieving the purpose of purifying water bodies. This technology uses catalysts to coordinate ozone oxidation to reduce the reaction activation energy or change the reaction process, thereby achieving the purpose of deep oxidation and maximizing the removal of organic pollutants. Ozone catalytic oxidation can be divided into homogeneous catalytic ozone oxidation and heterogeneous catalytic ozone oxidation according to different catalysts. Since the metal ions after the homogeneous catalytic ozone oxidation reaction are difficult to separate, the catalyst is lost, and the burden of subsequent treatment of the catalytic ozone oxidation reaction is increased, and the cost of wastewater treatment is increased. The catalyst of heterogeneous catalytic ozone oxidation exists in a solid state, which is easy to separate from water, can avoid the loss of catalyst, has the advantages of strong oxidizing property, simple operation, easy recovery and regeneration of catalyst, and small footprint, and has become one of the effective ways to treat wastewater.
[0005] Prior art public application number 202211571862.0, a method for inorganic treatment of radioactive TBP / OK organic waste liquid, the invention discloses a method for inorganic treatment of radioactive TBP / OK organic waste liquid, and relates to the technical field of radioactive waste treatment. It includes the following steps: S1: pre-treating and alkali washing the radioactive TBP / OK organic waste liquid; S2: fully mixing the TBP / OK organic waste liquid and hydrogen peroxide at a substance amount ratio of 4 to 6:1 and injecting them into a quartz glass reaction column; S3: placing an ultraviolet lamp into the quartz glass reaction column and turning it on, and at the same time, passing ozone into the quartz glass reaction column, and the mixed solution undergoes an oxidation reaction; S4: the generated tail gas is filtered through a nuclear-grade high-efficiency filter and discharged; S5: oil-water separation. The present invention utilizes the synergistic effect of hydrogen peroxide, ozone, and ultraviolet to produce ·OH with a high redox potential, which greatly improves the efficiency of oxidizing organic matter in TBP / OK organic waste liquid into small-molecule inorganic compounds. Through the above-mentioned comparative documents, it can be found that the existing preparation process is complicated and the preparation adjustment requirements are high, resulting in high use costs.
[0006] Heterogeneous catalysts are the main catalysts for ozone catalytic oxidation technology. Commonly used catalyst carriers include ceramic carriers, activated carbon and alumina, and the main active components are iron, copper, platinum, titanium and nickel. Heterogeneous ozone catalysts are generally in powdered or granular form, which can easily cause blockage. In addition, the specific surface area of the catalyst carrier is low, providing fewer active sites, which greatly reduces the effect of ozone catalytic oxidation. For environments where ozone is introduced for oxidation, the continuous injection of ozone will impact the catalyst, causing the catalyst to lose and reduce the oxidation efficiency. How to improve the ozone oxidation efficiency while ensuring the mechanical strength of the ozone catalyst is an issue that requires special attention.
[0007] In the research on heterogeneous catalysts for ozone oxidation, there are few reports on the use of molecular sieves as carriers, and no industrial applications are involved. Summary of the invention
[0008] The purpose of the present invention is to provide a heterogeneous ozone oxidation catalyst and apply it to inorganic treatment of organic waste liquid, in particular to inorganic treatment of radioactive tributyl phosphate / kerosene organic waste liquid.
[0009] An ozone oxidation catalyst for inorganic treatment of organic waste liquid is prepared according to the following weight parts: 2-25 parts of active metal oxide, 1-15 parts of modified element oxide, 40-80 parts of carrier and 15-40 parts of binder; The active metal oxides are manganese, nickel, platinum, and titanium metal oxides; the carrier is ZSM-5 molecular sieve, β molecular sieve, Y molecular sieve or a mixture thereof; the binder is alumina, aluminum sol, silica sol or a mixture thereof; and the modified element oxide is a combination of one or more oxides of iron, copper, cobalt, zinc, magnesium, calcium, and rare earth elements.
[0010] The silicon-aluminum ratio of the ZSM-5 molecular sieve is 10-500; the silicon-aluminum ratio of the β molecular sieve is 20-100; and the silicon-aluminum ratio of the Y-type molecular sieve is 1-10.
[0011] The silicon-aluminum ratio of the ZSM-5 molecular sieve is 20-200; the silicon-aluminum ratio of the β molecular sieve is 40-80; and the silicon-aluminum ratio of the Y-type molecular sieve is 2-5.
[0012] The modified element oxide is prepared by mixing water-soluble salts and acids, the water-soluble salts are nitrates, chlorides, oxalates or a mixture of multiple types; the water-soluble salts contain one or more combinations of iron, copper, cobalt, zinc, magnesium, calcium and rare earth elements.
[0013] A preparation method of an ozone oxidation catalyst for inorganic treatment of organic waste liquid comprises the following steps: mixing a carrier and a binder in proportion, forming and processing to obtain a strip catalyst carrier with a length of 2-5 mm and a diameter of 1.5 mm or a spherical catalyst carrier with a diameter of 1-3 mm, and standing at room temperature for 15-30 hours; drying at 60-120°C for 8-36 hours, and then roasting at 450-650°C for 1-6 hours, and then subjecting to water vapor aging treatment at 500-600°C for 1-4 hours to obtain the catalyst carrier; preparing a solution of an active metal oxide and a modifying element oxide, and impregnating the roasted catalyst carrier in the solution by an equal volume co-impregnation method for 6-24 hours, and then drying at 90-120°C in a drying oven for 4-12 hours, and then roasting in air at 500-600°C for 1-6 hours.
[0014] The method comprises standing at room temperature for 20-25 hours; drying at 70-100°C for 8-36 hours, and then drying at 500-600°C.
[0015] The catalyst prepared by the present invention is used for inorganic treatment of organic waste liquid, and the following beneficial effects can be obtained: The heterogeneous ozone oxidation catalyst provided by the present invention is easy to manufacture and use, and is conducive to reducing the manufacturing and use costs of the catalyst. The catalyst carrier is obtained by high-temperature calcination of a molecular sieve and a binder, and while ensuring mechanical strength, a larger specific surface area can be obtained, providing more active sites, thereby obtaining better catalytic activity, a long catalyst life, and good activity. When oxidizing organic waste liquid containing tributyl phosphate / kerosene, the COD removal rate can reach more than 90%. DETAILED DESCRIPTION
[0016] The embodiments of the present invention will be described in detail below in conjunction with the examples, the purpose of which is to better understand the present invention, but it will be appreciated by those skilled in the art that the following described embodiments are part of the present invention, rather than all of the embodiments, and therefore the embodiments do not limit the scope of protection of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work premises belong to the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to normal conditions or the conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be obtained by commercial purchase.
[0017] An ozone oxidation catalyst for inorganic treatment of organic waste liquid is prepared according to the following weight parts: 2-25 parts of active metal oxide, 1-15 parts of modified element oxide, 40-80 parts of carrier and 15-40 parts of binder; The active metal oxides are manganese, nickel, platinum, and titanium metal oxides; the carrier is ZSM-5 molecular sieve, β molecular sieve, Y molecular sieve or a mixture thereof; the binder is alumina, aluminum sol, silica sol or a mixture thereof; and the modified element oxide is a combination of one or more oxides of iron, copper, cobalt, zinc, magnesium, calcium, and rare earth elements.
[0018] The silicon-aluminum ratio of the ZSM-5 molecular sieve is 10-500; the silicon-aluminum ratio of the β molecular sieve is 20-100; and the silicon-aluminum ratio of the Y-type molecular sieve is 1-10.
[0019] The silicon-aluminum ratio of the ZSM-5 molecular sieve is 20-200; the silicon-aluminum ratio of the β molecular sieve is 40-80; and the silicon-aluminum ratio of the Y-type molecular sieve is 2-5.
[0020] The modified element oxide is prepared by mixing water-soluble salts and acids, the water-soluble salts are nitrates, chlorides, oxalates or a mixture of multiple types; the water-soluble salts contain one or more combinations of iron, copper, cobalt, zinc, magnesium, calcium and rare earth elements.
[0021] A preparation method of an ozone oxidation catalyst for inorganic treatment of organic waste liquid comprises the following steps: mixing a carrier and a binder in proportion, forming and processing to obtain a strip catalyst carrier with a length of 2-5 mm and a diameter of 1.5 mm or a spherical catalyst carrier with a diameter of 1-3 mm, and standing at room temperature for 15-30 hours; drying at 60-120°C for 8-36 hours, and then roasting at 450-650°C for 1-6 hours, and then subjecting to water vapor aging treatment at 500-600°C for 1-4 hours to obtain the catalyst carrier; preparing a solution of an active metal oxide and a modifying element oxide, and impregnating the roasted catalyst carrier in the solution by an equal volume co-impregnation method for 6-24 hours, and then drying at 90-120°C in a drying oven for 4-12 hours, and then roasting in air at 500-600°C for 1-6 hours.
[0022] The catalyst is allowed to stand at room temperature for 20-25 hours; dried at 70-100°C for 8-36 hours, and then dried at 500-600°C. The following is a detailed description of the heterogeneous ozone oxidation catalyst and its preparation method and its application in inorganic treatment of organic waste liquid according to the embodiment of the present invention: A heterogeneous ozone oxidation catalyst is mainly made of the following components in percentage by weight: 2-25 parts of active metal oxide; Modifying element oxide 0-15 parts; 40~80 copies of carrier; 15~40 parts of binder; The active metal oxide is one of manganese, nickel, platinum and titanium metal oxides; The modifying element is selected from one or more of copper, cobalt, zinc, iron, magnesium, calcium, and rare earth elements; The carrier is selected from one or more of ZSM-5 molecular sieve, β molecular sieve, and Y molecular sieve; The binder is selected from one or more of alumina, alumina sol and silica sol.
[0023] Example 1 360 g of ZSM-5 molecular sieve with a dry content of 90 silicon-aluminum ratio, 140 g of alumina and 160 g of deionized water were extruded into strips (2-5 mm long and about 1.5 mm in diameter) on a molding machine. oC Dry in oven for 4 hours and then at 600 oC calcined in air for 4 hours; then aged in a steam aging device for 2 hours, with a water weight hourly space velocity of 1h -1 The aging temperature is controlled at 550 oC, to obtain 500 g of the catalyst carrier; using 100 g / liter of manganese nitrate and 50 g / liter of iron nitrate mixed aqueous solution 200 ml equal volume of ferric nitrate impregnated 200 g of the catalyst carrier for 24 hours, at 90 oC After drying for 8 hours, transfer to a muffle furnace at 550 oC The catalyst was calcined in air for 5 hours to obtain Catalyst A, which contained 12.9% by weight manganese dioxide, 5.8% by weight ferric oxide, 58.6% by weight ZSM-5 molecular sieve and 22.7% by weight aluminum oxide.
[0024] Example 2 360 g of ZSM-5 molecular sieve with a dry content of 60 silicon-aluminum ratio, 140 g of alumina and 160 g of deionized water were extruded into strips (2-5 mm long and about 1.5 mm in diameter) on a molding machine. oC Dry in oven for 4 hours and then at 600 oC calcined in air for 4 hours; then aged in a steam aging device for 2 hours, with a water weight hourly space velocity of 1h -1 The aging temperature is controlled at 550 o C, to obtain 500 g of the catalyst carrier; using 60 g / liter of manganese nitrate and 40 g / liter of iron nitrate mixed aqueous solution 200 ml of equal volume of ferric nitrate impregnated 200 g of the catalyst carrier for 24 hours, at 90 oC After drying for 8 hours, transfer to a muffle furnace at 550 oC The catalyst was calcined in air for 5 hours to obtain a catalyst B, which contained 8.2% by weight manganese dioxide, 5.0% by weight ferric oxide, 62.5% by weight ZSM-5 molecular sieve and 24.3% by weight aluminum oxide.
[0025] Example 3 360 g of ZSM-5 molecular sieve with a dry content of 200 silicon-aluminum ratio, 140 g of alumina and 160 g of deionized water were extruded into strips (2-5 mm long and about 1.5 mm in diameter) on a molding machine. oC Dry in oven for 4 hours and then at 600 oC calcined in air for 4 hours; then aged in a steam aging device for 2 hours, with a water weight hourly space velocity of 1h -1 The aging temperature is controlled at 550 o C, to obtain 500 g of the catalyst carrier; using 150 g / liter of manganese nitrate and 80 g / liter of iron nitrate mixed aqueous solution 200 ml of equal volume of ferric nitrate impregnated 200 g of the catalyst carrier for 24 hours, at 90 oC After drying for 8 hours, transfer to a muffle furnace at 550 oCThe catalyst C was calcined in air for 5 hours, wherein the manganese dioxide content was 17.6% (weight), the iron oxide content was 8.5% (weight), the ZSM-5 molecular sieve content was 53.3% (weight), and the aluminum oxide content was 20.6% (weight).
[0026] Example 4 320 g of β molecular sieve with a dry content of 25% silicon-aluminum ratio, 180 g of alumina and 160 g of deionized water were extruded into strips (2-5 mm long and about 1.5 mm in diameter) on a molding machine. oC Dry in oven for 4 hours and then at 600 oC calcined in air for 4 hours; then aged in a steam aging device for 2 hours, with a water weight hourly space velocity of 1h -1 The aging temperature is controlled at 550 o C, to obtain 500 g of the catalyst carrier; using 80 g / liter of manganese nitrate and 40 g / liter of iron nitrate mixed aqueous solution 200 ml of equal volume of ferric nitrate impregnated 200 g of the catalyst carrier for 24 hours, at 90 oC After drying for 8 hours, transfer to a muffle furnace at 550 oC The catalyst was calcined in air for 5 hours to obtain catalyst D, which contained 10.7% by weight manganese dioxide, 4.8% by weight ferric oxide, 54.1% by weight ZSM-5 molecular sieve and 30.4% by weight aluminum oxide.
[0027] Example 5 400 g of Y molecular sieve with a dry content of 5% silicon-aluminum ratio, 100 g of alumina and 160 g of deionized water were extruded into strips (2-5 mm long and about 1.5 mm in diameter) on a molding machine. oC Dry in oven for 4 hours and then at 600 oC calcined in air for 4 hours; then aged in a steam aging device for 2 hours, with a water weight hourly space velocity of 1h -1 The aging temperature is controlled at 550 o C, to obtain 500 g of the catalyst carrier; using 120 g / liter of manganese nitrate containing manganese and 60 g / liter of iron nitrate mixed aqueous solution 200 ml equal volume impregnated 200 g of the catalyst carrier for 24 hours, at 90 oC After drying for 8 hours, transfer to a muffle furnace at 550 oC The catalyst was calcined in air for 5 hours to obtain Catalyst E, which contained 14.9% by weight manganese dioxide, 6.7% by weight ferric oxide, 62.7% by weight ZSM-5 molecular sieve and 15.7% by weight aluminum oxide.
[0028] Example 6 360 g of ZSM-5 molecular sieve with a dry content of 90 silicon-aluminum ratio, 140 g of alumina and 160 g of deionized water were extruded into strips (2-5 mm long and about 1.5 mm in diameter) on a molding machine. oC Dry in oven for 4 hours and then at 600 oC calcined in air for 4 hours; then aged in a steam aging device for 2 hours, with a water weight hourly space velocity of 1h -1 The aging temperature is controlled at 550 o C, to obtain 500 g of the catalyst carrier; using 100 g / liter of manganese nitrate containing manganese and 50 g / liter of cobalt nitrate mixed aqueous solution 200 ml of equal volume impregnated 200 g of the catalyst carrier for 24 hours, at 90 oC After drying for 8 hours, transfer to a muffle furnace at 550 oC The catalyst F was calcined in air for 5 hours, wherein the content of manganese dioxide was 12.9% (weight), the content of cobalt oxide was 5.2% (weight), the content of ZSM-5 molecular sieve was 58.9% (weight), and the content of aluminum oxide was 23.0% (weight).
[0029] Example 7 360 g of ZSM-5 molecular sieve with a dry content of 90 silicon-aluminum ratio, 140 g of alumina and 160 g of deionized water were extruded into strips (2-5 mm long and about 1.5 mm in diameter) on a molding machine. oC Dry in oven for 4 hours and then at 600 oC calcined in air for 4 hours; then aged in a steam aging device for 2 hours, with a water weight hourly space velocity of 1h -1 The aging temperature is controlled at 550 o C, to obtain 500 g of the catalyst carrier; using 100 g / liter of manganese nitrate containing manganese and 50 g / liter of copper nitrate mixed aqueous solution 200 ml of equal volume impregnated 200 g of the catalyst carrier for 24 hours, at 90 oC After drying for 8 hours, transfer to a muffle furnace at 550 oC The catalyst was calcined in air for 5 hours to obtain Catalyst G, which contained 13.0% by weight manganese dioxide, 5.1% by weight copper oxide, 59.0% by weight ZSM-5 molecular sieve and 22.9% by weight aluminum oxide.
[0030] Example 8 360 g of ZSM-5 molecular sieve with a dry content of 90 silicon-aluminum ratio, 140 g of alumina and 160 g of deionized water were extruded into strips (2-5 mm long and about 1.5 mm in diameter) on a molding machine. oC Dry in oven for 4 hours and then at 600 oCcalcined in air for 4 hours; then aged in a steam aging device for 2 hours, with a water weight hourly space velocity of 1h -1 The aging temperature is controlled at 550 o C, to obtain 500 g of the catalyst carrier; using 100 g / liter of nickel nitrate containing nickel and 50 g / liter of cobalt nitrate mixed aqueous solution 200 ml of equal volume impregnated 200 g of the catalyst carrier for 24 hours, at 90 oC After drying for 8 hours, transfer to a muffle furnace at 550 oC The catalyst F was calcined in air for 5 hours, wherein the nickel oxide content was 10.7% (weight), the cobalt oxide content was 5.3% (weight), the ZSM-5 molecular sieve content was 60.5% (weight), and the aluminum oxide content was 23.5% (weight).
[0031] Application Examples The performance of the ozone oxidation catalysts prepared in Examples 1 to 8 in the inorganic treatment of organic waste liquid was investigated in a tubular glass reactor. The organic waste liquid was a model organic waste liquid prepared with tributyl phosphate / kerosene (mass ratio of 3:7), and its COD value was about 5000 mg / L. 500 ml of the model organic waste liquid was charged into the tubular reactor, and then 50 g of the ozone catalyst was placed in the tubular reactor. An ozone mixed gas was introduced into the bottom of the tubular reactor. The ozone concentration was 100 mg / L, the mixed gas velocity was 1000 ml / min, the reaction temperature was 25 degrees, and the reaction time was 2 hours. After the reaction, the COD of the organic waste liquid was measured, and the COD removal rate was calculated. The results are shown in Table 1.
[0032] Table 1 Ozone catalyst reaction results .
Claims
1. An ozone oxidation catalyst for inorganic treatment of organic waste liquid, characterized in that Prepared in the following weight parts: 2-25 parts of active metal oxide, 1-15 parts of modifying element oxide, 40-80 parts of carrier and 15-40 parts of binder; The active metal oxides are manganese, nickel, platinum, and titanium metal oxides; the carrier is ZSM-5 molecular sieve, β molecular sieve, Y molecular sieve or a mixture thereof; the binder is alumina, aluminum sol, silica sol or a mixture thereof; and the modified element oxide is a combination of one or more oxides of iron, copper, cobalt, zinc, magnesium, calcium, and rare earth elements.
2. The ozone oxidation catalyst for inorganic treatment of organic waste liquid according to claim 1, characterized in that The silicon-aluminum ratio of the ZSM-5 molecular sieve is 10-500; the silicon-aluminum ratio of the β molecular sieve is 20-100; and the silicon-aluminum ratio of the Y-type molecular sieve is 1-10.
3. The ozone oxidation catalyst for inorganic treatment of organic waste liquid according to claim 2, characterized in that The silicon-aluminum ratio of the ZSM-5 molecular sieve is 20-200; the silicon-aluminum ratio of the β molecular sieve is 40-80; and the silicon-aluminum ratio of the Y-type molecular sieve is 2-5.
4. The ozone oxidation catalyst for inorganic treatment of organic waste liquid according to claim 1, characterized in that The modified element oxide is prepared by mixing water-soluble salts and acids, the water-soluble salts are nitrates, chlorides, oxalates or a mixture of multiple types; the water-soluble salts contain one or more combinations of iron, copper, cobalt, zinc, magnesium, calcium and rare earth elements.
5. The method for preparing an ozone oxidation catalyst for inorganic treatment of organic waste liquid according to any one of claims 1 to 4, characterized in that The method comprises the following steps: mixing a carrier and a binder in proportion, and after forming and processing, obtaining a strip-shaped catalyst carrier with a length of 2-5 mm and a diameter of 1.5 mm or a spherical catalyst carrier with a diameter of 1-3 mm, and standing at room temperature for 15-30 hours; drying at 60-120°C for 8-36 hours, and then roasting at 450-650°C for 1-6 hours, and then subjecting the catalyst carrier to water vapor aging treatment at 500-600°C for 1-4 hours to obtain the catalyst carrier; preparing a solution of an active metal oxide and a modifying element oxide, and using an equal volume co-impregnation method to immerse the roasted catalyst carrier in the solution for 6-24 hours, and then drying it in a drying oven at 90-120°C for 4-12 hours, and then roasting it in air at 500-600°C for 1-6 hours.
6. The method for preparing an ozone oxidation catalyst for inorganic treatment of organic waste liquid according to claim 5, characterized in that The step of standing the mixture at room temperature for 20-25 hours, drying the mixture at 70-100°C for 8-36 hours, and then drying the mixture at 500-600°C.
Citation Information
Patent Citations
Inorganic treatment method for radioactive TBP / OK organic waste liquid
CN115798766A